(untitled) (Journal of International Studies, 2013)
Монгол-Оросын худалдааны эргэлтийн бууралтад нөлөөлж буй хүчин зүйлс, манай улсын ОХУ руу нийлүүлж буй экспортын болон ОХУ-аас авч буй импортын барааны бүтэц, ОХУ ДХБ-ын гишүүнээр элсэн орсноор манай хоёр улсын худалдаанд шинэ боломж нээгдэнэ. The New Opportunities for Mongolian and Russian trade relations The factors influencing the reduction of trade between Mongolia and Russia, structure of Mongolia’s exports to Russia, Mongolia’s imports from Russia, the new challenges Mongolian and Russian trade relations after Russian joins to the WTO.